Sistem Informasi Pengaduan Perbaikan Jalan Desa (Program SIG) Berbasis Web - Hidayat Muhammad Nur; Vadlya Maarif (Computer Science (CO-SCIENCE), 2023)
Several damaged roads in the Kebasen area during the rainy season are continuous work for the government. As an effort to assist this public service, it provides an opportunity for the public to submit complaints or complaints when public facilities have not met expectations. The following is an alternative to the procedure for submitting complaints or complaints for road repairs online which can help better communication. This study aims to build a GIS web-based road repair complaint information system. The system prototype was designed in stages with the development of the waterfall model system and the PHP programming language. In making this system the author uses the framework CodeIgniter (Ci) and Object Oriented Analysis and Design (OOAD). The interface for connecting several applications uses the Google Application Programming Interface (API) and MySQL database. The results of this study are expected to be the system of choice for conveying the aspirations of the people up to date in complaints about road repairs, environmental conditions, traffic conditions, public road management conditions, security conditions, street lighting conditions and presenting information optimally